Impact of Parameter Uncertainty on Power Flow accuracy in multi-terminal systems - Beddard,A; Wang,W; Barnes,M; Green,TC; Green,PR (IEEE, 2016)
Accurate power flow in a MT system can be achievedwith droop controllers. However, almost all publications haveassumed that the DC voltage, DC current and DC cableresistances can be measured with 100% accuracy. In this paper, anovel power flow solver is developed which enables the user toanalyse the impact of these parameters on power flow accuracy.The developed Parameter Uncertainty Power Flow Solver (PUPFS)is shown to be able to accurately calculate the power flowerror for hundreds of parameter uncertainty scenarios in lessthan a second. The PU-PFS is employed to investigate the impactof parameter uncertainty on a potential MT system and theresults show that realistic measurement errors (0.2%) can resultin significant power flow error (>150MW). Finally, the paperassesses the key factors which influence the power flow accuracyresulting in a number of important conclusions.